2019
DOI: 10.1111/fcsr.12332
|View full text |Cite
|
Sign up to set email alerts
|

What's in the Box? Investigation of Beauty Subscription Box Retail Services

Abstract: The purpose of this study was to explore key attributes that may influence customers’ behavioral intentions toward beauty subscription box retail services (SBRS). The Stimulus‐Organism‐Response paradigm was used as a conceptual framework for examining the relationships among variables, such as product‐related attributes (Stimuli), attitude (Organism), Word of Mouth (WOM), and repurchase intention (Response). A total of 357 useable responses were collected through an online survey, administered on Amazon Mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Furthermore, consumer attitudes toward subscription-based online services (SOS) were observed to mediate the relationship between utilitarian motivation, hedonic motivation, consumer innovativeness, and use intention. Lee et al [ 36 ] performed a quantitative study to identify the main stimuli (product price, quality, assortment, uniqueness, and surprise) that influence consumer loyalty and found that product quality and uniqueness affected consumer attitudes toward products in the subscription economy. Finally, Bray et al [ 15 ] explained that given different characteristics, consumer attitudes and behaviors can vary depending on the type of subscription service under consideration.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Furthermore, consumer attitudes toward subscription-based online services (SOS) were observed to mediate the relationship between utilitarian motivation, hedonic motivation, consumer innovativeness, and use intention. Lee et al [ 36 ] performed a quantitative study to identify the main stimuli (product price, quality, assortment, uniqueness, and surprise) that influence consumer loyalty and found that product quality and uniqueness affected consumer attitudes toward products in the subscription economy. Finally, Bray et al [ 15 ] explained that given different characteristics, consumer attitudes and behaviors can vary depending on the type of subscription service under consideration.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Perea y Monsuwé et al (2004) suggested that consumers' attitudes toward online shopping reflect characteristics of each individual and product, as well as the ease of use and enjoyment of the online interface and usefulness of the product. In the context of the subscription retail, Lee et al (2019) demonstrated that product-level factors (i.e. product quality, assortment and uniqueness) influenced consumers' attitudes toward the subscription service.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Despite this apparent fit, very few studies (e.g. Lee et al , 2019; Ramkumar and Woo, 2018; Woo and Ramkumar, 2018) have investigated what profile of Gen-Y men desire to receive a subscription box, and no past studies have examined why subscription boxes are so popular among this group.…”
Section: Introductionmentioning
confidence: 99%
“…Quality consciousness refers to a person's perception of the quality of a product (Lang et al, 2013). Subscription service provides consumers high quality products in a monthly box (Lee et al, 2019). Price consciousness refers to an individual's sensitivity to price when purchasing products (Lang & Armstrong, 2016), and it also implies that consumers are not willing to pay a higher price (Lichtenstein et al, 1993).…”
mentioning
confidence: 99%
“…Price consciousness refers to an individual's sensitivity to price when purchasing products (Lang & Armstrong, 2016), and it also implies that consumers are not willing to pay a higher price (Lichtenstein et al, 1993). As subscription-box service is a simple online business model, it provides new items of apparel brands with a lower price (Lee et al, 2019). Consumer environmental knowledge refers to "factual information that individuals have about the environment, the ecology of the planet, and the influence of human actions on the environment" (Arcury & Johnson, 1987, p. 32).…”
mentioning
confidence: 99%